2010
DOI: 10.1016/j.jep.2010.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Typhonium flagelliforme induces apoptosis in CEMss cells via activation of caspase-9, PARP cleavage and cytochrome c release: Its activation coupled with G0/G1 phase cell cycle arrest

Abstract: Collectively, results presented in this study demonstrated that the DCM/F7 fraction inhibited the proliferation of leukemia cells, leading to the programmed cell death, which was confirmed to be through the mitochondrial pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…A recent study reported that MCPH1 is involved in E2F1-mediated apoptosis; knockdown of MCPH1 in HEK293 cells resulted in decreased expression of E2F1 target genes, such as caspase-3, caspase-7, BRCA1 and Chk1 (23), which are important in cell apoptosis. Mitochondria participate in the intrinsic apoptotic pathway and tumors arise more frequently through the intrinsic pathway than the extrinsic pathway as a result of the sensitivity of the intrinsic pathway to apoptosis (24). In the intrinsic pathway, apoptosis is mediated by proteins in the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that MCPH1 is involved in E2F1-mediated apoptosis; knockdown of MCPH1 in HEK293 cells resulted in decreased expression of E2F1 target genes, such as caspase-3, caspase-7, BRCA1 and Chk1 (23), which are important in cell apoptosis. Mitochondria participate in the intrinsic apoptotic pathway and tumors arise more frequently through the intrinsic pathway than the extrinsic pathway as a result of the sensitivity of the intrinsic pathway to apoptosis (24). In the intrinsic pathway, apoptosis is mediated by proteins in the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs studied for leukemia therapy include Hibiscus cannabinus [3], Vernonia amygdalina root [4] Euphorbia formosana [5], Allium sativum [6], Moringa oleifera [7] and Typhonium flagelliforme [8]. Morinda citrifolia (Noni) or `mengkudu' in Malaysia has been extensively used for its broad therapeutic effects, including various anticancer activities, in both clinical practice and laboratory animal models [9].…”
Section: Introductionmentioning
confidence: 99%
“…The extract dose dependently induced leukemia cells apoptosis both in vitro and in vivo restored all pathological blood, liver and spleen changes in vivo and reinstated the endogenous immune responses to normal healthy levels in vivo. [7] and Typhonium flagelliforme [8]. Morinda citrifolia (Noni) or `mengkudu' in Malaysia has been extensively used for its broad therapeutic effects, including various anticancer activities, in both clinical practice and laboratory animal models [9].…”
mentioning
confidence: 99%
“…Cleaved procaspase-8 may either directly activate caspase-3 or induce the cleavage of p22/BID, the BH-3 domain-only sub-group of BCL-2 family, to generate a truncated p15 BID (tBID). The truncated p15BID translocates to the mitochondria and promotes the release of Cyt c. 6,7 In the receptor-independent mechanism, multiple pro-apoptotic signals converge at the mitochondrial level to cause the release of Cyt c from the mitochondria. Cyt c synergistically acts with Apaf-1 to activate caspase-9, and subsequently release caspase-3.…”
mentioning
confidence: 99%